The Influence of Work Engagement and Job Satisfaction on Employee Performance with Competence as an Intervening Variable for BPJS Employment Employees in Aceh Province - Roza Fonna, Erfira; Farida Ferine, Kiki (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to determine the effect of Work Engagement and Job Satisfaction on Employee Performance with Competence as an intervening variable. This research uses associative quantitative research. This research was conducted at the Aceh Province BPJS office. The population of this research was 100 employees and the researcher wanted to take all the population as a sample. researchers used a saturated sampling technique to make all employees into the sample, the tool for calculating research results used smart PLS version 3.3.3. data collection techniques by distributing questionnaires and surveys, this research model is path analysis. Based on the results of the research that has been carried out and data analysis as explained in the previous chapter, the following conclusions are presented from the research results as follows: Job Satisfaction has a positive and insignificant effect on Employee Performance, Job Satisfaction has a negative and insignificant effect on Competency, Competency has a positive and significant effect on Employee Performance, Work Engagement has an insignificant negative effect on Employee Performance, Work Engagement has an insignificant positive effect on Competency, Job Satisfaction has an insignificant negative effect on Employee Performance through Competency, Work Engagement has an insignificant positive effect on Employee Performance through Competency.